Linking ethylene co-monomer content and stereostructure to polycrystallinity and foam density of random copolymers of polypropylene. (6th January 2021) - Pin, Jean-Mathieu; Tuccitto, Anthony V.; Shivokhin, Maksim E.; Lee, Patrick C.
Abstract: Static batch foaming is used in a model investigation aiming to understand and predict the impact of resin molecular structure on the foamability of random copolymers of polypropylene (RCP) for bead foam applications. The foaming behavior of seven polypropylene based resins with ethylene content varying from 0 to 11 mol% can be categorized into two groups related to their respective degrees of regio-defects: below 0.1 and around 0.66 mol%. Increasing the ethylene content from 0 to 4.04 mol% is enough to decrease the foam density by a factor of 6.3, as well as the foaming temperature by 15 °C. For a specific number of stereo and regio-defects, the ethylene content has a linear response with the optimal foaming temperature. Regio-defect impact exhibits a similar linear behavior; however, it is decoupled from ethylene content effects. A hierarchical relationship between the polycrystallinity and the foam mechanism was then drawn. The stress induced by the foam cell growth was shown to provoke the generation of more ordered crystalline structure, adding another layer of complexity in obtaining foams with the desired density. Graphical abstract: Image 1 Highlights: Increasing ethylene content/RCPs structural defects reduce the foaming temperature. Increasing ethylene content reduces the RCPs lowest reachable foam density. There is a linear relationship between ethylene content and foaming temperature. A Gaussian model was built to predict the optimal foaming temperature. Stress induced foam cell growth generate more ordered crystals.